2005
DOI: 10.1021/ie050484d
|View full text |Cite
|
Sign up to set email alerts
|

Defluidization Conditions for a Fluidized Bed of Iron Oxide-, Nickel Oxide-, and Manganese Oxide-Containing Oxygen Carriers for Chemical-Looping Combustion

Abstract: For combustion with CO2 capture, chemical-looping combustion with inherent separation of CO2 is a promising technology. Chemical-looping combustion uses oxygen carriers that are composed of metal oxide to transfer oxygen from the combustion air to the fuel. The defluidization of oxygen-carrier particles was investigated to improve the understanding of when particle agglomeration may occur. The study was made in a laboratory fluidized-bed reactor at 950 °C, simulating a chemical-looping combustion system by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 17 publications
3
90
0
Order By: Relevance
“…As it was pointed out, some authors have found agglomeration problems working with Fe-bases OCs [17][18]. However, although a high degree of conversion was reached in the batch fluidized reactor the carrier did not show any agglomeration behaviour during operation.…”
Section: Batch Fluidized Bed Reactormentioning
confidence: 89%
See 1 more Smart Citation
“…As it was pointed out, some authors have found agglomeration problems working with Fe-bases OCs [17][18]. However, although a high degree of conversion was reached in the batch fluidized reactor the carrier did not show any agglomeration behaviour during operation.…”
Section: Batch Fluidized Bed Reactormentioning
confidence: 89%
“…Other chemical characteristics are advantageous for the use of Fe-based oxygen carriers: low tendency to carbon deposition [12] and no risk of sulphide or sulphate formation at any concentration or operating temperature when sulphur containing fuels are used [13]. [17][18] To develop a suitable oxygen carrier, synthetic materials, low-cost minerals, ores and waste products have been evaluated. There are several studies working with synthetic Fe-based oxygen carriers using different supports, (sepiolite, SiO 2 , TiO 2 ZrO 2 and Al 2 O 3 ), different preparation methods, and metal contents [14][15][16]19].…”
Section: Introductionmentioning
confidence: 99%
“…First, because complete fuel conversion to CO 2 and H 2 O can thermodynamically not be reached anymore [12,13]. Second, because those phases are known to have a high tendency to form agglomerates [14][15][16].…”
Section: Iron Oxide Scalementioning
confidence: 99%
“…until steam was added to the fuel flow, carbon deposition in the fuel line occurred. The reaction that is believed to be responsible is known as the Boudouard reaction, see equation (14).…”
Section: Ilmenitementioning
confidence: 99%
“…Figures 6 and 9, might be an indicator for coke formation on the oxygen carrier. Carbon formation on manganesebased oxygen carrier with methane as fuel has been mentioned in earlier studies [16,28,29], whereas oxygen release properties of C2Z-1050 oxygen carrier might have inhibited coke formation on the particles to a large extent.…”
Section: Carbon Leakage and Possible Coke Formationmentioning
confidence: 82%